Solve for $x$:


My attempt:

The L.H.S is equal to $\dfrac{1+\sqrt{4x+1}}{2}$ and R.H.S equals $x^2$

Equating both sides:

$\implies 4x+1=(2x^2-1)^2$

$\implies 4x+1=4x^4-4x^2+1$

$\implies 4x^4-4x^2-4x=0$

$\implies x(x^3-x-1)=0$

Disregarding the complex roots,

$\implies x=0$ 0r $\dfrac{1}{3}\sqrt[3]{\dfrac{27-3\sqrt{69}}{2}}+\dfrac{\sqrt[3]{\dfrac{9+\sqrt{69}}{2}}}{3^{2/3}}$

Is my solution correct? By the way I would like to see other methods to solve it. Thanks!

  • $\begingroup$ I am not getting that the RHS = x^2 $\endgroup$ – bobbym Aug 5 '14 at 13:40
  • $\begingroup$ $\sqrt{xa}=a \implies \sqrt{x} = \sqrt{a} \implies x=a$, i.e. R.H.S = $x$. $\endgroup$ – Daniel R Aug 5 '14 at 13:42
  • $\begingroup$ Those exponents sum to 1 not 2. I think the RHS = x. $\endgroup$ – bobbym Aug 5 '14 at 13:42
  • $\begingroup$ We have 62 questions tagged nested-radicals, many of which are relevant to your question. $\endgroup$ – MJD Aug 5 '14 at 13:44
  • $\begingroup$ Not that it matters, but the complex form can be rewritten as: $$\frac{1}{3}\left(\sqrt[3]{\dfrac{27-3\sqrt{69}}{2}} + \sqrt[3]{\dfrac{27+3\sqrt{69}}{2}}\right)$$ which is a little clearer. It doesn't matter because of the error evaluating the RHS. $\endgroup$ – Thomas Andrews Aug 5 '14 at 13:47

I get a different solution:

Let $y = \sqrt{x+\sqrt{x+\sqrt{x+\sqrt{x+..}}}}=\sqrt{x\sqrt{x\sqrt{x\sqrt{x...}}}}$.

Then $y^2 = x+ y$ and $y^2 = xy$.

From the second equation we see that $x = y = 0$ is a possible solution, otherwise, $x = y \neq 0$.

So from the first equation: $x^2 = 2x \Rightarrow x = y = 2$

  • $\begingroup$ I'd also got that. The way the asker's done it, it should be $x\sqrt{x\sqrt{x\sqrt{...}}}$ on the RHS to get their solution. $\endgroup$ – Jam Aug 5 '14 at 13:43
  • 1
    $\begingroup$ My God!! What have I done!!!!!!! $\endgroup$ – Tom Lynd Aug 5 '14 at 13:44
  • $\begingroup$ From the second equation we got $x = y$ so I sustituted $y$ for $x$ on the first equation. $\endgroup$ – Darth Geek Aug 5 '14 at 13:47

Note that RHS is wrong: $$y=\sqrt{x\sqrt {x\cdots}}\implies y^2=x\sqrt{x\sqrt {x\cdots}}=xy\implies y=0 \text{ or }x$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.